2013
DOI: 10.5430/jst.v3n4p22
|View full text |Cite
|
Sign up to set email alerts
|

The role of disparity-mutagenesis model on tumor development with special reference to increased mutation rate

Abstract: Human solid tumors are believed to have very high mutation rates at least in the early stage of extension. Irrespective of whether the increased mutation rate is a necessary condition for the tumor development or not, extremely high mutation rates such as in excess of the so-called "threshold" would before long result in the natural death of tumor cells. In reality, however, we are dying by cancer. Thus, it has been hypothesized that tumor cells should make a quick transition from the higher mutation state to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It has been shown that Paramecia can become extinct by the accumulation of harmful mutations when cultured for a long period without conjugations (Holmes and Holmes, 1986 ). As mentioned above, however, our disparity mutagenesis model predicts an increased mutation rate threshold; i.e., in the case of the knapsack problem without sex (Wada et al, 1993 ), in our evolution experiments with living microorganisms (Tanabe et al, 1999 ; Shimoda et al, 2006 ) and in the case of human tumor expansion (Furusawa, 2013 ). These systems were carried out without relation to sex.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It has been shown that Paramecia can become extinct by the accumulation of harmful mutations when cultured for a long period without conjugations (Holmes and Holmes, 1986 ). As mentioned above, however, our disparity mutagenesis model predicts an increased mutation rate threshold; i.e., in the case of the knapsack problem without sex (Wada et al, 1993 ), in our evolution experiments with living microorganisms (Tanabe et al, 1999 ; Shimoda et al, 2006 ) and in the case of human tumor expansion (Furusawa, 2013 ). These systems were carried out without relation to sex.…”
Section: Discussionmentioning
confidence: 76%
“…The disparity mutagenesis model is deduced from the principles of the “Disparity Theory of Evolution” (Furusawa and Doi, 1992 , 1998 ; Furusawa, 2013 ) and provides an explanation for why living things do not become extinct even when mutation rates exceed the threshold. The theory and model predict that the error frequency is significantly higher in the lagging DNA strand, since a more complex system is used in the synthesis of the lagging strand compared to that of the leading strand (Furusawa and Doi, 1992 ).…”
Section: How the Disparity-mutagenesis Model Increases The Threshold mentioning
confidence: 99%
See 1 more Smart Citation